Comparative environmental impacts analysis of technologies for recovering critical metals from copper anode slime: Insights from LCA - Yu Li; Jenny Baker; Yaxi Fang; Haizhou Cao; Cameron Pleydell-Pearce; Trystan Watson; Sha Chen; Guangling Zhao (Environmental Chemistry and Ecotoxicology)
Copper anode slime (CAS) is a byproduct produced during copper electrorefining process. It contains metals such as gold, silver, copper, selenium, tellurium etc. Without proper treatment, CAS posed significant environmental hazard due to its toxic components. Recovering critical metals from CAS not only mitigates environmental risks but also serves as an important source of these valuable materials. Recycling of critical metals can significantly enhance metal recycling efficiency and support the advancement of a circular economy. However, this process could introduce potential environmental impacts due to the increased consumption of energy, chemical material, and water. The process requires comprehensive assessment. In this study, life cycle assessment is employed to evaluate the potential environmental impact of the four resource recovery processes for copper anode slime: pyrometallurgy, hydrometallurgy, semi-hydrometallurgy, and combining bio-hydrometallurgy and semi-hydrometallurgy (CBS). The functional unit is 1 kg of copper anode slime. 5 metals are recycled during the process named: cupper (Cu), tellurium (Te), selenium (Se), gold (Au), and silver (Ag). Six impact categories—climate change, freshwater ecotoxicity, marine ecotoxicity, terrestrial ecotoxicity, human toxicity (cancer), and human toxicity (non-cancer)—were assessed and compared across the four recycling technologies. The LCA results show that CBS has the lowest environmental impact among all the assessed impact categories. CBS process demonstrated superior metal recovery rates. Hydrometallurgy has the lowest energy and material costs. CBS incurs higher total costs due to the use of expensive chemicals like potassium iodide.